Mental Toughness and Its Relationship with Sports Achievement Motivation Among Professional Football Players in Palestine - Hussein, Raed F. (Advances in Social Sciences Research Journal, 2023)
This study aims to identify mental toughness and its relationship with sports achievement motivation among professional football players in Palestine, as well as to identify the differences between the levels of mental toughness and sports achievement motivation among professional football players in Palestine attributed to the variables of club level and years of experience. To achieve this, the study was conducted on a sample of (146) professional football players in Palestine, who were selected in a randomized, stratified manner. The researcher used the descriptive approach which was appropriate for the nature of the study and its questions. He also used the Mark Atkinson (2014) scale for Mental Toughness and the Achievement Motives Scale by (Anne-Marie Elbe & Franziska Wenhold (2005). The results revealed that the total levels ofthe hope of success and fear of failure scopes among professional football players in Palestine were high. They also revealed that there was a statistically significant positive correlation at a significance level of (α ≤ 0.01) between mental toughness and sports achievement motivation among professional football players in Palestine. The results also showed a statistically significant correlation between mental toughness and the scopes of hope of success and fear of failurerelated to sports motivation achievement among players, and showed that there were no statistically significant differences at a significance level (α ≤ 0.05) between mental toughness and sports achievement motivation among professional football players in Palestine attributed to the variables of professionallevel and years of experience.